Implementation of the human papillomavirus school-entry requirement in Puerto Rico: barriers and facilitators using the consolidated framework for implementation research - Vivian Colón-López; Roxana Soto-Abreu; Diana T. Medina-Laabes; Olga L. Díaz-Miranda; Ana P. Ortiz; Erick L. Suárez; Pamela C. Hull (Taylor & Francis Group, 2021)
In 2018, Puerto Rico (PR) enacted a Human papillomavirus (HPV) vaccine school-entry requirement for students ages 11 to 12. Using the Consolidated Framework for Implementation Research (CFIR), we aimed to identify potential barriers and facilitators of this implementation. We conducted 38 qualitative interviews with stakeholders in PR from different organizations (Department of Health, Schools, Healthcare Providers, and Community organizations). We evaluated construct rating variability between the organizations to determine barriers and facilitators. The strongest facilitator determined was stakeholder's awareness of the parent's and student's needs to meet the HPV school-entry requirement. Other facilitators included initiatives for school-entry policies and the relative advantage of this requirement over different strategies. The strongest barriers included was the cost for private providers to administer the HPV vaccine, the negative influence of social media about the vaccine, which affected parents' acceptance, and the lack of school nurses as available staff resources for the school entry requirement. Findings from this study can be used to improve implementation (adaptations/modifications) and inform other states and countries in earlier stages of consideration of the adoption of similar immunization policies. Most barriers can be modifiable with the implementation of educational programs/training across schools, considering that they are the first line of response to parents of this school entry requirement.